Model Case-Based Learning Berbasis Digital: Inovasi dalam Pendidikan di Sekolah Dasar - Wulan, Rayung; Muhajir, Achmad; Ali, Nur (Universitas Indraprasta PGRI Jakarta, 2024)
The Case-Based Learning model is known as an effective method for developing contextual understanding and critical thinking skills of students. In the current digital era, the use of digital devices has opened up new opportunities in presenting and managing case-based learning in a more interactive and interesting way. This activity aims to present the use of digital devices in case-based learning to educators. This learning model is expected to improve educators' understanding and skills in integrating digital tools into case-based learning. This research uses descriptive qualitative methods. By using descriptive qualitative methods, researchers can provide a rich and contextual picture of the phenomena that occur. The aim of the research is an effort to improve the quality of learning by utilizing digital devices. Education in the digital era requires innovative approaches to improve the quality of learning and student engagement. SDN 05 Pasar Baru, Central Jakarta, implements the Case-Based Learning (CBL) model, which utilizes digital tools to answer challenges. By facing and overcoming existing challenges, this model can continue to be improved and adapted to meet educational needs in the digital era.